2020
DOI: 10.1016/j.phanu.2020.100208
|View full text |Cite
|
Sign up to set email alerts
|

A critical appreciation of intangible resources in PharmaNutrition

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This information can be used in promoting or advertising phytosterol enriched foods and supplements; notably, as already mentioned, it is reasonable to assume that a professional support, where possible medical, to the use of these formulations, formally classified as “food” could significantly improve the appropriateness of their use [ 49 , 50 ].…”
Section: Regulatory Frameworkmentioning
confidence: 99%
“…This information can be used in promoting or advertising phytosterol enriched foods and supplements; notably, as already mentioned, it is reasonable to assume that a professional support, where possible medical, to the use of these formulations, formally classified as “food” could significantly improve the appropriateness of their use [ 49 , 50 ].…”
Section: Regulatory Frameworkmentioning
confidence: 99%
“…A similar trend was found in a previous study comparing patents and clinical trials (Wiegers et al, 2022). This result could be expected, as clinical trials are a later step in the research process than patents (van de Burgwal et al, 2018). To clarify, patents are intended to protect new ideas and products whereas clinical trials can be considered tools for further development and testing of a product.…”
Section: Discussionmentioning
confidence: 99%
“…A closer look at the clinical trial data that were collected reveals that all clinical trials executed in Iran were sponsored by academia, which is in accordance with the finding that patents were mainly applied for by the industry and clinical trials were mainly sponsored or executed by academia. This is a likely outcome because patent applications can be costly and time consuming, and therefore are usually done with the expectations of profits in the long run (van de Burgwal et al, 2018). Clinical trials on the other hand are usually executed to test the safety and efficacy of a product on a shorter term, with a higher focus on acquiring scientific knowledge instead of profits (Janse et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is further evidenced by the fact that PhaNu industry analyses have shown that innovation barriers result from a lack of cross-industry understanding and appreciation of relevant intangibles and of the necessary dynamic capabilities to absorb and integrate these into innovation processes [49,258]. Novel approaches are needed to build critical managerial appreciation of IC, its components, and their relation to key topics on the managerial agenda such as improving absorptive capacity [46], innovation, value creation and appropriation [296,297]. Specifically, demands have been articulated for boundary-spanning IC conceptualizations-robust enough to bear relevance between organizations, plastic enough to adapt to situated particularities of individual cases-to close a gap between IC theory and practice [22,68,105,125,298].…”
Section: Te C Hnov a Ti On Under Reviewmentioning
confidence: 99%